A nonlinear PID control scheme for hard disk drive servosystems - Isayed, B.M.; Hawwa, M.A. (2007 Mediterranean Conference on Control and Automation, 2007)
The aim of this paper is to put forward a novel design of a nonlinear PID controller type based on carefully choosing nonlinear gains to enable reducing the settling time, minimizing the overshoot and improving the required control effort during the functions of the read/write (R/W) head positioning servomechanism in hard disk drives. The controller is capable of adjusting a driving force, a damping effect and an integral action according to the position of the actual system output with respect to the desired output. This is carried out by utilizing the three actions of the PID controller which are tuned by different nonlinear functions to provide the system with the needed level of a driving force, a damping and a steady-state error correction action. Simulation results, including step function response, control signal history, and a disturbance rejection capability are presented to show the efficiency of the proposed controller.